Analysis of the sustainability of paddy rice farming in Percut Sei Tuan District - Amalia Fauziah Hulwani; Diana Chalil; Rungrat Saeyang (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2026)
Rice paddy farming plays a strategic role in supporting regional food security, especially in Deli Serdang Regency, one of the rice production centres in North Sumatra Province. However, pressure from land conversion, excessive use of chemical inputs, and limited technological and institutional support have the potential to threaten the sustainability of paddy rice farming. This study aims to analyse the sustainability status of paddy rice farming and identify sensitive attributes in the ecological, economic, social, institutional, technological, and infrastructure dimensions in the Percut Sei Tuan district. The analytical method used was Multi-Dimensional Scaling (MDS) with the RAP-PADI software. The research was carried out in Tanjung Rejo Village, Cinta Damai Village and Percut Village by involving 100 respondents of paddy rice farmers. The results showed that rice field farming in the Percut Sei Tuan District has a multidimensional value of 57.16 (quite sustainable). The ecological dimension has one sensitive attribute: the use of chemical inputs. The economic dimension has one sensitive attribute: farmers' profits. The social dimension has three sensitive attributes: farming experience, farmers' motivation to farm, and farmer education. In the institutional and legal dimensions, there is one sensitive attribute: farmers' access to government assistance. The technology and infrastructure dimensions have two sensitive attributes: response to technology and village farming roads.